2006
DOI: 10.1016/j.acn.2006.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Standardized assessment of cognitive functioning during development and aging using an automated touchscreen battery

Abstract: This study examined the effects of age, gender and education on subjects spanning nine decades on a new cognitive battery of 12 tests. One thousand and seven participants between 6 and 82 completed the battery under standardized conditions using an automated, computerized touchscreen. Sensitive indicators of change were obtained on measures of attention and working memory, learning and memory retrieval, and language, visuospatial function, sensori-motor and executive function. Improvement tended to occur throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 58 publications
7
99
2
Order By: Relevance
“…Vakil et al (2010) observed better female performance on many verbal memory measures. Similarly, Clark et al (2006) observed better performance in females on memory tasks, whereas males performed better on motor tasks. A gender difference was found only in the A6 list in which 10-year-old girls performed better than boys.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Vakil et al (2010) observed better female performance on many verbal memory measures. Similarly, Clark et al (2006) observed better performance in females on memory tasks, whereas males performed better on motor tasks. A gender difference was found only in the A6 list in which 10-year-old girls performed better than boys.…”
Section: Discussionmentioning
confidence: 91%
“…A gender difference was found only in the A6 list in which 10-year-old girls performed better than boys. Other studies have found better performance in girls on RAVLT (Anderson & Lajoie, 1996;Kramer et al, 1997;Clark et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The integneuro battery has previously been shown to consist of strong validity and reliability (McFarlane et al 2005;Paul et al 2005;Williams et al 2005), and has established norms (Clark et al 2006). The instructions and practice trials were administered immediately before completing each task.…”
Section: Materials and Equipmentmentioning
confidence: 99%
“…The IntegNeuro battery has sound psychometric properties in terms of reliability, validity, cross-cultural consistency, and age, sex and education norms. [67][68][69] Core cognitive domains were established previously using factor analytic techniques: information processing speed, verbal memory, response speed (sensori-motorfunction), sustained attention, working memory, verbal processing and executive function 70 (see Supplementary Table 3 for details of factor loadings and cognitive measures defining each domain). Factor scores were inverted (where necessary) such that a high score reflected superior performance (that is, fewer errors and faster reaction time).…”
Section: Syndromal Depression and Anxiety Symptomsmentioning
confidence: 99%